Anatomía comparada del leño de Maytenus en el Noroeste de Argentina (Sudamérica) - Giménez, Ana María; Moglia, Juana Graciela; Figueroa, M. E.; Díaz-Zírpolo, J. A.; Calatayu, Federico (Instituto de Ecología, A.C., 2014)
Comparative wood anatomy of Maytenus in Northwestern Argentina (South America)This paper is a comparative wood anatomy study of four species of the genus Maytenus living in Northwest Argentina: Maytenus vitisidaea,M. viscifolia, M. spinosa and M. cuezzoi. The specimens were collected in Santiago del Estero and Salta, Argentina and wood samplesare safeguarded in the collection of the LAM (Laboratory of Wood Anatomy), Faculty of Forestry of Santiago del Estero University(UNSE), Argentina. The terminology used followed the IAWA List of Microscopic Features for Hardwood Identification. The diagnosticfeatures of wood anatomical characters were evaluated by employing statistical methods such as Cluster Analysis (CA) and PrincipalComponent Analysis (PCA). PCA showed vessel diameter, fibre wall, and ray width to be significant variables. CA showed M. cuezzoi andM. viscifolia to have the highest affinity.